Efeitos da época de plantio sobre três cultivares de trigo sob irrigação por aspersão - de Abreu Vilela, Enivanis; Starling Brandão, S; M del Giudice, Renato; S Sediyama, Carlos; A Cardoso, Antônio (Revista Ceres, 2025)
The effect of different planting times on grain yield and other characteristics in three varieties of wheat with different vegetative cycles was studied in Viçosa, Minas Gerais, Brazil, in order to determine the best planting season for the crop in a rice-wheat-rotation scheme under sprinkle irrigation. The cultivars ‘Pel A 506-62’, “LAS-49', and ‘Nadadores’ were sown March 20, April 10, April 30 and May 20.